Biological Magnetic Materials and Applications (Springer Singapore, 2018)
This book addresses the biologically controlled synthesis of magnetic materials, and its applications in bio-inspired design and synthesis. It highlights several key aspects of biologically produced magnetic materials - (i) organisms that biologically synthesize and utilize magnetic materials; (ii) formation mechanisms; (iii) how these biological formation routes yield various phases and morphologies; and (iv) the resultant magnetic and structural properties - and describes diverse bio-inspired approaches to utilizing magnetic materials in applications ranging from semiconductor to health industries. In addition, the book discusses the recent industrial use of magnetic materials to develop scalable technologies that encompass protein displays, drug-delivery, biophysical separations, and medical diagnostics, as well as outlining future next-generation applications. As such, it offers valuable insights for all scientists interested in using multidisciplinary fields to overcome current obstacles, and in gaining multifaceted expertise in magnetic materials bionanotechnology.